2013
DOI: 10.3109/00365521.2012.758770
|View full text |Cite
|
Sign up to set email alerts
|

Sphincter training or anal injections of dextranomer for treatment of anal incontinence: a randomized trial

Abstract: The efficacy of anal injections and biofeedback in treating anal incontinence did not differ in this randomized, single-blinded, controlled trial.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(27 citation statements)
references
References 23 publications
(32 reference statements)
0
27
0
Order By: Relevance
“…Treatment did not significantly improve FI quality of life; data for complete continence and effects on anorectal physiology or imaging were not provided 80, 81 . Another controlled trial with 126 patients reported significant improvement in FI symptom severity and QOL in patients who were randomized to pelvic floor biofeedback therapy and separately to NASHA Dx 82 ; the efficacy of these approaches was not different. Biofeedback therapy increased anal squeeze pressure but NASHA Dx did not increase anal resting or squeeze pressre.…”
Section: Fecal Incontinencementioning
confidence: 99%
“…Treatment did not significantly improve FI quality of life; data for complete continence and effects on anorectal physiology or imaging were not provided 80, 81 . Another controlled trial with 126 patients reported significant improvement in FI symptom severity and QOL in patients who were randomized to pelvic floor biofeedback therapy and separately to NASHA Dx 82 ; the efficacy of these approaches was not different. Biofeedback therapy increased anal squeeze pressure but NASHA Dx did not increase anal resting or squeeze pressre.…”
Section: Fecal Incontinencementioning
confidence: 99%
“…NASHA Dx has been evaluated in several trials (Table 3),108–119 including a randomized, double-blind sham-controlled study in adults who had failed conservative therapies. Patients received NASHA Dx (n=136) or sham treatment (n=70) in an outpatient setting without anesthesia; patients with no persistent AEs but persistent FI after 1 month were offered 1 retreatment procedure 109.…”
Section: Resultsmentioning
confidence: 99%
“…Efficacy and long-term durability have been reported in open-label studies110114 and a comparative study versus biofeedback training (∼20 min daily, 5 d a week, for 6 mo; Table 3). 108…”
Section: Resultsmentioning
confidence: 99%
“…Dextranomer microspheres in non-animal stabilized hyaluronic acid (NASHA Dx) is the only Food and Drug Administration (FDA)-approved product for FI 23 . While the implied mechanism of action is to enhance the seal of the anal canal, dextranomer did not significantly increase anal resting or squeeze pressures nor was it superior to biofeedback therapy 24 . In a randomized, double-blind sham-controlled study in adults who had failed conservative therapies, 71/136 (52%) patients in the active treatment group vs. 22/70 (31%) in the sham group had a treatment response (≥50% improvement from baseline in the number of FI episodes) at 6 months (OR: 2.36; P = 0.0089) 25 (Table 1).…”
Section: Perianal Bulking Injectionmentioning
confidence: 87%